Hubungan Kecerdasan Naturalistik dengan Asesmen Sumatif Biologi Peserta Didik Fase E di SMAN 4 Sumatera Barat - Rahmiyeti, Rahmiyeti; Fuadiyah, Sa’diatul (Lembaga Yasin AlSys, 2023)
Learning achievement can be seen from the summative assessment obtained by students after the learning process. One of the factors that influence the assessment results of learners is intelligence. The level of each intelligence possessed by learners is different. Naturalistic intelligence is an important intelligence in learning biology. Naturalistic intelligence is one of the 9 theories of intelligence proposed and developed by Howard Gardner (Harvard Psychologist). This study aims to determine the relationship between naturalistic intelligence and summative assessment of students of SMAN 4 West Sumatra. This type of research is descriptive correlational research. The population in this study were all Phase E students of SMAN 4 West Sumatra. The sample in this study amounted to 86 students in Phase E who were taken by total sampling technique. Data collection techniques through naturalistic intelligence questionnaire and for learning outcomes obtained from mid-semester summative assessment. Data analysis techniques using the analysis requirements test and correlation test using Pearson product moment. Based on the results of hypothesis testing, it can be concluded that there is a positive and significant relationship between naturalistic intelligence and learning outcomes of Phase E students at SMAN 4 West Sumatra, with a correlation coefficient value of 0.326 which is classified into the low category.